1989
DOI: 10.1152/ajpregu.1989.256.6.r1264
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow, oxygenation, and carbohydrate metabolism in immature fetal sheep in utero

Abstract: Studies of cerebral blood flow (CBF) and metabolism in fetal sheep have been largely confined to late gestation, a time when brain development in this species is largely complete. Few studies have been done at a time when the fetal sheep brain is in the midst of rapid differentiation and development. We studied seven fetal sheep in utero at 91 days of gestation (term = 145-150 days) 24 h after catheters were placed into the sagittal sinus, axillary artery, and inferior vena cava. We measured CBF by the microsp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 0 publications
5
35
0
Order By: Relevance
“…laboratories, and there is a high correlation of flows determined by radio-and fluorescent-labeled microspheres (Glenny et al, 1993;Bernard et al, 2000). Under basal conditions, our blood flow measurements in white and gray matter agreed closely with those obtained with radioactive microspheres (Szymonowicz et al, 1988(Szymonowicz et al, , 1990Gleason et al, 1989).…”
Section: Quantification Of Cbf In Developing Brainsupporting
confidence: 80%
“…laboratories, and there is a high correlation of flows determined by radio-and fluorescent-labeled microspheres (Glenny et al, 1993;Bernard et al, 2000). Under basal conditions, our blood flow measurements in white and gray matter agreed closely with those obtained with radioactive microspheres (Szymonowicz et al, 1988(Szymonowicz et al, , 1990Gleason et al, 1989).…”
Section: Quantification Of Cbf In Developing Brainsupporting
confidence: 80%
“…Another advantage of the fetal sheep model is that physiological studies can be performed at a critical stage of brain development, i.e., 90 days of gestation, in which there is brain growth and onset of organized electrocortical activity preceding a period of intense neuroglial multiplication and myelination (17). Finally, previous cerebrovascular studies in immature fetal sheep demonstrate that they have lower CBF and CMRO 2 as well as limited autoregulation and blunted responses to hypoxemia compared with near-term fetuses (9,10,13). A limitation of this model is the potential difficulty in extrapolating results obtained in fetuses to newborns, particularly the influence of the uteroplacental circulation and fetal physiology on the cerebrovascular and systemic responses we observed.…”
Section: Discussionmentioning
confidence: 99%
“…After the skin was prepared with povidone-iodine (Betadine), the uterus was exposed through a midline abdominal incision. The fetal head and limbs were exposed one at a time through small uterine incisions for placement of fetal catheters into the inferior vena cava (IVC, via pedal veins), the brachiocephalic trunk (via axillary arteries), the brachial/axillary vein, and the superior sagittal sinus by previously described methods (9,10). A catheter (Tygon tubing) was sewn to the fetal ear to measure amniotic fluid pressure and to administer ampicillin (500 mg).…”
Section: Surgical Preparationmentioning
confidence: 99%
“…More recent measurements have shown that in normoxic fetal sheep, CBF and metabolism are modulated by its electroencephalographic ally de fined sleep-arousal state (Clapp, 1980;Richardson et aI., 1985b;Chao et aI., 1989b), with a small amount of anaerobic glucose metabolism appearing during the more metabolically active, low-voltage state. It also seems that more immature sheep fetuses studied be fore the development of distinguishable EEG arousal states consume glucose in excess of what can be ox idized and excrete lactate (Gleason et al, 1989).…”
Section: Controlmentioning
confidence: 99%